2019
DOI: 10.3390/diagnostics9020063
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CTRP3 Plasma Concentrations Are Associated with Sepsis and Predict Mortality in Critically Ill Patients

Abstract: C1q/ tumor necrosis factor (TNF)-like protein 3 (CTRP3) represents a novel member of the adipokine family that exerts favorable metabolic actions in humans. However, the role of CTRP3 in critical illness and sepsis is currently unknown. Upon admission to the medical intensive care unit (ICU), we investigated CTRP3 plasma concentrations in 218 critically ill patients (145 with sepsis, 73 without sepsis). Results were compared with 66 healthy controls. CTRP3 plasma levels were significantly decreased in critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…In human critical illness, circulating CTRP3 levels were found to be reduced. In a cohort of n = 218 patients, both critically ill patients with ( n = 145) or without ( n = 73) sepsis had significantly decreased plasma CTRP3 levels compared with healthy controls [38]. Moreover, low CTRP3 levels were directly associated with the presence of sepsis among ICU patients.…”
Section: Selected Adipokines With a Potential Role In Critical Illmentioning
confidence: 99%
See 1 more Smart Citation
“…In human critical illness, circulating CTRP3 levels were found to be reduced. In a cohort of n = 218 patients, both critically ill patients with ( n = 145) or without ( n = 73) sepsis had significantly decreased plasma CTRP3 levels compared with healthy controls [38]. Moreover, low CTRP3 levels were directly associated with the presence of sepsis among ICU patients.…”
Section: Selected Adipokines With a Potential Role In Critical Illmentioning
confidence: 99%
“…In line, CTRP3 plasma concentrations were inversely correlated with inflammatory cytokines and standard markers of sepsis such as CRP and PCT. Importantly, the authors described a direct association between low CTRP3 levels (<620.6 ng/mL) and an increased overall mortality [38]. Although these data need to be confirmed in further trials, it suggests a clinically relevant role of CTRP3 as a potential new diagnostic and prognostic biomarker in patients with critical illness and sepsis.…”
Section: Selected Adipokines With a Potential Role In Critical Illmentioning
confidence: 99%
“…Interestingly, other studies reported that CTRP3 is the only adipokine in septic patients that decreases significantly compared to such proteins as ghrelin, resistin, leptin, and CTRP1 [ 36 , 37 , 38 , 39 ]. Another study showed that metabolic comorbidities did not affect the CTRP3 dynamic in the setting of critical illness [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nos estudos sobre os efeitos da CTRP3 no sistema cardiovascular mostra-se que: i) reduz o estresse oxidativo, ii) inibe a apoptose, iii) tem efeitos anti-inflamatórios e antiaterogênicos, iv) reduz o desenvolvimento de fibrose, v) inibe a gliconeogênese e, como resultado de todos esses efeitos, a CTRP3 reduz as chances de desenvolver doenças cardiovasculares (CV). [2][3][4][5][6][7][8][9]15,16 Considerando seus efeitos atuais, observou-se que a CTRP3 pode, em termos fisiopatológicos, proteger e melhorar os aspectos clínicos de pacientes com DAC. Níveis séricos de CTRP3 foram avaliados em pacientes com insuficiência cardíaca com fração de ejeção reduzida (ICFEr), SCA, angina estável e dissecção aórtica aguda; e os níveis sérios de CTRP3 foram significativamente menores.…”
Section: Discussionunclassified